Courting her secret heart - Davis, Mary, 1963- (Davis, Mary, 1963- Prodigal daughters., 2018)
Deborah Miller lives a double life as an Amish woman<U+2014>and a fashion model! All photography is forbidden in her Plain community, so she must keep her job a secret. But when Amos Burkholder starts helping at her family<U+2019>s farm, hiding the truth from him is impossible. And soon she must choose between the Englischer world of modeling and the Amish man she<U+2019>s come to love.